2023
DOI: 10.1002/adom.202301197
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Reversible On‐Off Switching of Aggregation‐Induced Emission via LCST Phase Transition of Ionic Liquids in Water

Abstract: A new phosphonium‐based ionic liquid is designed and synthesized using the 1,1,2,2‐tetraphenylethene‐derived anion ([P4444]4[TSPE]). Aqueous solutions of [P4444]4[TSPE] are obtained as transparent liquids (monophasic state), which suspended with increasing temperature. This behavior is found to exhibit a lower critical solution temperature (LCST) phase transition behavior. The LCST phase transition temperature can be controlled from 36 to 55 °C by changing the weight ratio between [P4444]4[TSPE] and water. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…It is known that the luminescence of AIEgens may be influenced by temperature, [44][45][46][47] which has been exploited in the measurement of the glass transition temperature 48,49 and the upper or lower critical solution temperature of polymers. [50][51][52] Previously, we embedded an AIEgen, i.e., tetra(4-nitrophenyl) ethylene (TPE-4N), into silicone, and found that its photoluminescence intensity is sensitive to the environmental temperature. 43 Although the characteristic is promising for the fabrication of dual temperature-and pressure-sensitive coatings, two issues need to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the luminescence of AIEgens may be influenced by temperature, [44][45][46][47] which has been exploited in the measurement of the glass transition temperature 48,49 and the upper or lower critical solution temperature of polymers. [50][51][52] Previously, we embedded an AIEgen, i.e., tetra(4-nitrophenyl) ethylene (TPE-4N), into silicone, and found that its photoluminescence intensity is sensitive to the environmental temperature. 43 Although the characteristic is promising for the fabrication of dual temperature-and pressure-sensitive coatings, two issues need to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…9 The responsiveness of these ionogels is generally derived from the combined effects of responsive polymers, ionic liquids (ILs), or the compatibility between these components. 10–15 For example, mechano-responsive ionogels with tunable color and shape have been prepared by incorporating spiropyran-based polymers into the gel matrix. 16,17 By virtue of the design ability of ILs, a variety of stimuli-responsive ILs have been synthesized, providing a versatile platform for creating smart ionogels with reversible color change.…”
mentioning
confidence: 99%